Impact of Sustainable Development Goals (SDGs) on Quality Education Impacting other SDGs in Pakistan Higher Education Institutions: Moderation and Mediation of Resource Slack and Shared Vision Capability - Bashir Ahmad; Azam Anwar Khan; Maawra Salam; Rahat Anwar Khan (Sustainable Business and Society in Emerging Economies)
Purpose: This paper seeks to review and analyze the progress made in the attainment of Sustainable Development Goal (SDGs) as set by the United Nations in 2015 with focus on SDG-4 i.e., Quality Education impacting the others.